Training suppliers by delegating workers: A decision support model. (March 2016) - Glock, Christoph H.
Highlights: The paper studies a supply chain consisting of a single vendor and a single buyer. The buyer has the option to train the supplier by delegating workers. A decision support model is developed for supplier training. The qualification of the buyer's and the supplier's workforce are determinants of supplier training. Abstract: This paper studies a scenario where a buyer sourcing a product from a single supplier has the option to train the supplier. It is assumed that learning occurs both in the workforce of the supplier and the buyer, and that the buyer may delegate some of its workers to the supplier for a certain time span to help realizing performance improvements there. The paper develops a formal model of supplier training that helps to determine the optimal number of workers delegated as well as the timing and duration of supplier training. The model is analyzed in a numerical experiment, and guidelines for supplier training are derived. It is shown that the relative cost structure at the buyer and the supplier as well as the learning characteristics of the supplier's and the buyer's workforce are important parameters that should be considered when planning supplier training activities.